2021
DOI: 10.3399/bjgpo.2021.0096
|View full text |Cite
|
Sign up to set email alerts
|

Understanding GPs’ views and experiences of using clinical prediction rules in the management of respiratory infections: a qualitative study

Abstract: Background:Respiratory tract infections (RTIs) account for 60% of antibiotic prescribing in primary care. Several clinical prediction rules (CPRs) have been developed to help reduce unnecessary prescribing for RTIs, but there are a lack of studies exploring whether or how these CPRs are being used in UK general practice.Aim:To explore UK GPs’ views and experiences with regards to RTI CPRs and to identify barriers and facilitators to their use in practice.Design & setting:A qualitative analysis of interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Some were established strategies, such as Treat Antibiotics Responsibly; Guidance, Education (TARGET) ( 28 , 41 , 53 ), antibiotics review kit (ARK) ( 37 ), Health Alliance for Prudent Prescribing, Yield and Use of Antimicrobial Drugs in the Treatment of Respiratory Tract Infections (HAPPY AUDIT) ( 60 , 61 ), Genomics to combat Resistance against Antibiotics in Community-acquired LRTI in Europe Internet TRaining for antibiOtic use (GRACE INTRO) ( 27 , 81 ) and Converting Habits of Antibiotic Use for Respiratory Tract Infections in German Primary Care (CHANGE-3) ( 72 , 74 ), while some were bespoke antimicrobial stewardship programmes ( 23 , 26 , 30 , 34 , 35 , 38 , 42 , 46 , 47 , 49 , 52 , 58 , 59 , 62–66 , 68 , 69 , 77–80 ). C-reactive protein point-of-care testing was often reported ( 26 , 27 , 33 , 34 , 40 , 50 , 51 , 56–59 , 70 , 76 , 81 ). The majority of the studies ( n = 51) reported that interventions include a patient interactive component in the form of posters, leaflet, videos, interactive decision support tools ( Table 1 ; Appendix 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some were established strategies, such as Treat Antibiotics Responsibly; Guidance, Education (TARGET) ( 28 , 41 , 53 ), antibiotics review kit (ARK) ( 37 ), Health Alliance for Prudent Prescribing, Yield and Use of Antimicrobial Drugs in the Treatment of Respiratory Tract Infections (HAPPY AUDIT) ( 60 , 61 ), Genomics to combat Resistance against Antibiotics in Community-acquired LRTI in Europe Internet TRaining for antibiOtic use (GRACE INTRO) ( 27 , 81 ) and Converting Habits of Antibiotic Use for Respiratory Tract Infections in German Primary Care (CHANGE-3) ( 72 , 74 ), while some were bespoke antimicrobial stewardship programmes ( 23 , 26 , 30 , 34 , 35 , 38 , 42 , 46 , 47 , 49 , 52 , 58 , 59 , 62–66 , 68 , 69 , 77–80 ). C-reactive protein point-of-care testing was often reported ( 26 , 27 , 33 , 34 , 40 , 50 , 51 , 56–59 , 70 , 76 , 81 ). The majority of the studies ( n = 51) reported that interventions include a patient interactive component in the form of posters, leaflet, videos, interactive decision support tools ( Table 1 ; Appendix 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study among HCPs in paediatric emergency department in Canada reported that participants were unaware of their prescribing pattern and the scale and scope of the challenge of implementing antimicrobial stewardship in the emergency department ( 36 ). HCPs’ lack of awareness of the available interventions were also described ( 50 , 53 , 63 , 72 , 74 , 76 , 77 ). For example, many general practitioners in the United Kingdom were not aware of the Royal College of General Practitioners (RCGP) TARGET online courses and so they have not used them ( 53 ).…”
Section: Provider Level Factorsmentioning
confidence: 99%
See 3 more Smart Citations